Peran Kepemimpinan Kiai di Pendidikan Pesantren dalam Menghadapi Revolusi Industri 4.0 - Asnawan Asnawan; Sulaiman Sulaiman (STAIFAS-Press, 2020)
This paper discusses the role of the kiai's leadership in pesantren education in an effort to strengthen the Industrial Revolution 4.0 industry. Pesantren is an ideal education system that attempts to provide education to the community to develop the existing potential, because pesantren santri in pesantren are not only given religious knowledge, santri are also taught to live independently, have character and innovate through pesantren activities. The pesantren is one of the institutions of Islamic education that will produce a generation of Indonesians into 'ulama', Muslim scholars and generations who have national character and morality. In the current era of information technology development, learning approaches have experienced rapid development that can change people's mindsets. The availability of information technology that is connected to the internet makes it easy for everyone to access science. So that pesantren must also be able to actualize these developments by developing pesantren curricula that are in accordance with the needs of the times. Then what is the role of pesantren in facing the development of globalization, what strategies are suitable in dealing with generations of the millennial era.